Carotid sinus syncope treated by pacing. Analysis of persistent symptoms and role of atrioventricular sequential pacing. Issue 5 (May 1982) - Morley, C A; Perrins, E J; Grant, P; Chan, S L; McBrien, D J; Sutton, R
Abstract : Seventy patients have been paced for carotid sinus syndrome over four years. Twelve patients had persistent symptoms despite adequate ventricular pacing. Patients with persistent symptoms were found to have a significant vasodepressor response, a significant hypotensive response to ventricular pacing (pacemaker effect), and a severe hypotensive response to carotid sinus massage with introduction of ventricular pacing, which reproduced symptoms in all patients. A group of 14 asymptomatic paced carotid sinus patients was found to have a significantly lower vasodepressor response, pacemaker effect, and combined vasodepressor response plus pacemaker effect than the group with persistent symptoms. Atrioventricular sequential pacing was shown to eliminate the hypotensive effect of ventricular pacing and is considered to be the treatment of choice for patients with carotid sinus syndrome who have both cardioinhibitory and significant vasodepressor responses.